Metástases de carcinoma de mama em cadelas: avaliação da técnica de linfonodo sentinela - Beserra, Hugo Enrique Orsini [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Microscopic evaluation of lymph nodes in bitches with mammary carcinomas may have fundamental importance in guidance the therapy since lymphatic drainage constitutes the most common route for metastasis. In recent years, several techniques have been used to detect and remove Sentinel Lymph Nades (SLN) based on the principIe of stepwise progression of cancer and lymphatic drainage. In human medicine, SLN biopsy and analysis constitutes the main prognostic factor in women with mammary , carcinomas. This study was designed to evaluate, in an unprecedented manner, the accuracy of sentinel lymph no de biopsy in bitches with mammary carcinomas. Forthyone dogs with no predilection for breed or age, with previous cytological diagnosis of mammary carcinoma were submitted to inoculation of patent blue V dye in peritumoral skin, followed by radical mastectomy and radicallymphadenectomy. Lymphanedectomy included sentinel and non- sentinel lymph nades in order to detect lymph nade metastasis. Both groups were compared in order to determine the accuracy of SLN technique in the detection of node metastasis. The lymph nades were subject to a standard serial sectioning method, stained by routine H&E or submitted to immunohistochemistry using pan-cytokeratins AEl/AE3 and the myoepitelial marker CK14. Nineteen animaIs (46.3%) had nodal metastasis. Sensibility and specificity for SLN technique were 89.5 % and 100 %, respectively, with a kappa value of 0.90 (p<O.OOOl). Therefore, SLN biopsy offers high sensitivity in the early diagnosis of lymph no de metastasis allowing a more accurate clinical staging. These results probably impacts on greater chances of patient survival

A avaliação microscópica dos linfonodos em cadelas portadoras de carcinoma de mama pode desempenhar um papel fundamental no direcionamento terapêutico, já que a drenagem linfática representa a via mais comum de metástases. Nos últimos anos tem-se desenvolvido técnicas que oferecem excelente acurácia na remoção dos linfonodos, como a Técnica do Linfonodo Sentinela (TLS), que se baseia no princípio de progressão escalonada na drenagem linfática de neoplasias e que atualmente é o principal fator prognóstico e diagnóstico em mulheres portadoras de carcinomas de mama. O objetivo da pesquisa foi avaliar de forma inédita a acurácia da biópsia do linfonodo sentinela em cadelas portadoras de carcinoma de mama. Foram utilizadas 41 cadelas com diagnóstico citológico do tumor. Após injeção do corante azul patente V, procedeu-se a mastectomia, juntamente com a linfadenectomia (sentinelas e não sentinelas). O material foi submetido a cortes seriados e avaliado microscopicamente pela coloração rotineira de H&E e imuno-histoquímica com os marcadores para pan-citoqueratina AE1/AE3 e células mioepiteliais CK14, que revelou que 46,3% (19/41) dos animais apresentavam metástase nodal. Os valores de sensibilidade e especificidade encontrados para a TLS foram de 89,5% e 100%, respectivamente, com índice kappa igual a 0,90 e p<0,0001. Portanto, a TLS oferece alta sensibilidade no diagnóstico precoce de micrometástases, permitindo maior precisão no estadiamento do paciente oncológico e consequentemente, maiores chances de sobrevida
Keywords: Cão - Doenças; Mamas - Cancer; Gânglios linfáticos - Biópsia; Metastase; Mastectomia; Breast Cancer